Correlation between changeover from weak antilocalization (WAL) to weak localization (WL) and positive to negative magnetoresistance in S-doped Bi1.5Sb0.5Te1.3Se1.7 - Singh M.; Ghosh L.; Gangwar V.K.; Kumar Y.; Pal D.; Shahi P.; Kumar S.; Mukherjee S.; Shimada K.; Chatterjee S. (My University, 2025)
The magneto-transport and angle-resolved photoelectron spectroscopy (ARPES) of the S-doped Bi1.5Sb0.5Te1.3Se1.7 system have been investigated. Both the positive magnetoresistance (pMR) and negative magnetoresistance (nMR) under a perpendicular magnetic field as well as a changeover from weak antilocalization (WAL) to weak localization (WL) are observed. The interplay between pMR and nMR is elucidated in terms of the dephasing and spin-orbit scattering time scales. The topological surface state bands have been explored using ARPES. © 2022 Author(s).